Analyzing Gait With Minimal Body-Worn Sensing: Combining UWB and IMU - Wouda, Frank J.; Sakthivelu, Uthvag; Bilal, Ibrahim (IEEE sensors journal, 2025)
Gait disorders are seeing an increase in incidence due to the aging world population. To improve mobility in daily life, it is necessary to accurately monitor gait parameters using body-worn devices. However, current device setups are either too complex or inaccurate. To that end, we propose to combine ultrawideband (UWB) and inertial measurement units (IMUs) technology as a portable setup on the feet of the user. An extended Kalman filter (EKF) was implemented to fuse the distance information (from UWB) with the integration of acceleration and angular velocity measurements to obtain relative foot positions that do not suffer from integration drift. Our results show that spatiotemporal parameters are estimated with higher accuracy (mean step length relative (to the body height of the subject) root mean squared error (rRMSE) = 0.037, step width rRMSE = 0.049, FIA RMSE = 4.0°, and FPA RMSE = 3.4°) using the combination of UWB and IMU sensors compared to using IMUs only: mean step length rRMSE = 0.198, step width rRMSE = 0.456, FIA RMSE = 4.0°, and FPA RMSE = 3.3°.